CDK1 Prevents Unscheduled PLK4-STIL Complex Assembly in Centriole Biogenesis - Zitouni, Sihem (2016)
Centrioles are essential for the assembly of both centrosomes and cilia. Centriole biogenesis occurs once and only once per cell cycle and is temporally coordinated with cell-cycle progression, ensuring the formation of the right number of centrioles at the right time. The formation of new daughter centrioles is guided by a pre-existing, mother centriole. The proximity between mother and daughter centrioles was proposed to restrict new centriole formation until they separate beyond a critical distance. Paradoxically, mother and daughter centrioles overcome this distance in early mitosis, at a time when triggers for centriole biogenesis Polo-like kinase 4 (PLK4) and its substrate STIL are abundant. Here we show that in mitosis, the mitotic kinase CDK1-CyclinB binds STIL and prevents formation of the PLK4-STIL complex and STIL phosphorylation by PLK4, thus inhibiting untimely onset of centriole biogenesis. After CDK1-CyclinB inactivation upon mitotic exit, PLK4 can bind and phosphorylate STIL in G1, allowing pro-centriole assembly in the subsequent S phase. Our work shows that complementary mechanisms, such as mother-daughter centriole proximity and CDK1-CyclinB interaction with centriolar components, ensure that centriole biogenesis occurs once and only once per cell cycle, raising parallels to the cell-cycle regulation of DNA replication and centromere formation.